Heart rate variability in patients with agoraphobia with or without panic disorder remains stable during CBT but increases following in-vivo exposure. (May 2019) - Mumm, Jennifer Lara Maria; Pyrkosch, Lena; Plag, Jens; Nagel, Patrick; Petzold, Moritz Bruno; Bischoff, Sophie; Fehm, Lydia; Fydrich, Thomas; Ströhle, Andreas
Highlights: Heart rate variability increases during in-vivo exposure. Heart rate shows a trend to decreases during in-vivo exposure. Cognitive behavioral therapy does not change resting heart rate. Cognitive behavioral therapy does not change resting heart rate variability. Abstract: Patients with anxiety disorders have a lower heart rate variability (HRV) than healthy controls. Low HRV is associated with cardiovascular disease and dysfunction of the autonomic nervous system (ANS). The aim of the present study was to investigate if HRV in patients with agoraphobia with or without panic disorder can be influenced by cognitive behavioral therapy (CBT). 73 patients with agoraphobia with or without panic disorder were included in the study. Heart rate (HR) and HRV were recorded at rest before and after CBT and during in-vivo exposure. No changes in HR and HRV were observed throughout therapy. During in-vivo exposure HRV increased significantly and HR exhibited a tendency to decrease. Despite clinical improvement of anxiety symptoms, ANS activity at rest did not seem to be influenced by CBT. However, during in-vivo exposure, HRV changed significantly, indicating a higher parasympathetic activity at the end of exposure.